Relationship between match statistics, game outcome and pre-match hormonal state in professional rugby union - Gaviglio, C. M.; James, N.; Crewther, B. T.; Kilduff, L. P.; Cook, C. J (International Journal of Performance Analysis in Sport, 2013)
The first aim of this investigation was to determine if performance indicator (PI) scores generated from rugby union game statistics discriminated between outcomes. Thirty one elite professional rugby games were analysed. For each game three cumulative PI scores were generated based upon skill actions (SkillPI), aggressive actions (AggPI) and an additive combination of AggPI and SkillPI (SkAggPI). Only the aggressive based PI score (AggPI) showed significant difference between outcome (p<0.01). The second aim of the study was to determine the PI's relationship with game-day salivary testosterone and cortisol concentrations across a sub-set of 6 games. The testosterone to cortisol (T/C) ratio and the change from pre to post (peri) hormone concentrations were also calculated and used during analysis. AggPI showed a strong correlation with pre testosterone (r=0.86, p<0.05), pre T/C (r=0.86, p<0.05) and peri testosterone (r=-0.87, p<0.05). The finding of this study speculates that in this team pre-match testosterone concentrations may be one factor contributing to a favourable aggressive-based PI score and thus outcome. Therefore, understanding how and when different PI's contribute to match outcome and its relationship with pre-match hormonal state potentially opens up new strategies for coaching and player management leading up to match play.